2020
DOI: 10.1055/s-0040-1715505
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Experience of Obstetric Patients and Health Care Workers after Implementation of Universal SARS-CoV-2 Testing

Abstract: Objective This study was aimed to describe the hospitalization and early postpartum psychological experience for asymptomatic obstetric patients tested for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) as part of a universal testing program and report the impact of this program on labor and delivery health care workers' job satisfaction and workplace anxiety. Study Design This is a cohort study of asymptomatic pregnant women who underwent SARS-CoV-2 testing between April 13, 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 6 publications
2
66
1
17
Order By: Relevance
“…Organising childcare was recommended as a form of support for HCWs [ 106 , 115 ], and work-life balance was reported to decrease the extent of the psychological consequences of the pandemic on HCWs [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Organising childcare was recommended as a form of support for HCWs [ 106 , 115 ], and work-life balance was reported to decrease the extent of the psychological consequences of the pandemic on HCWs [ 116 , 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…As highlighted by our findings, the most traumatic elements of these women’s experiences were the sudden family separation, self-isolation, the partner not allowed to be present at birth and the use of masks and gloves in the physical interaction with the newborn. A mixed-method cohort study by Bender et al (2020) similarly identifies neglect, isolation and neonatal separation as difficult aspects of COVID-19 positive women’s experiences of birth [ 18 ]. The theme named ‘pandemic relationships’ is the one to which the interviewed women gave most attention when recounting their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, most pregnant women who tested negative thought that prenatal SARS‐CoV‐2 screening tests could decrease anxieties about the viral infection to themselves, their offspring, and their families. In contrast, Bender et al reported that, in Philadelphia, about 72% of asymptomatic pregnant women who tested negative felt no change in the already existing fear or anxiety 14 . The difference in maternal feelings about prenatal PCR testing between these two areas is probably attributed to the higher prevalence of COVID‐19 in Philadelphia than in Fukui.…”
Section: Discussionmentioning
confidence: 96%